Lubricating components
Patent Information
- Application Number
- JP2025058634
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明の潤滑組成物は、潤滑性及び耐剥離性に優れる。
Smart Images

Figure 2026165960000001 
Figure 2026165960000002 
Figure 2026165960000003
Abstract
Description
[Technical Field]
[0001] This invention relates to a dilutable lubricating composition. [Background technology]
[0002] As described in the inventions in Patent Documents 1 and 2, fluorine solvent-diluted lubricating compositions are known. Fluorine solvent-diluted lubricating compositions are applied to sliding parts of automobiles, precision equipment, and other devices to improve lubrication. For example, a fluorine solvent-diluted lubricating composition is composed of a fluorine oil as a base oil and a solid lubricant dissolved or dispersed in a fluorine solvent. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2020-105329 [Patent Document 2] Japanese Patent Publication No. 2010-184995 [Overview of the project] [Problems that the invention aims to solve]
[0004] However, in applications using fluorine solvent-diluted lubricating compositions, the lubricity of these compositions was not necessarily high, as squeaking noises tended to occur after a relatively short number of sliding cycles. Furthermore, fluorine compounds such as fluorine solvents are difficult to decompose, raising concerns about their impact on the environment.
[0005] Furthermore, there was a need for a dilutable lubricating composition that would not peel off even when exposed to high temperature and high humidity environments.
[0006] Therefore, the present invention has been made in view of the above problems, and aims to provide a lubricating composition that is excellent in lubricity and peel resistance, as an alternative to fluorine solvent-diluted lubricating compositions. [Means for Solving the Problems]
[0007] The lubricating composition of the present invention contains at least a solvent and a lubricating component, wherein the solvent comprises water, an organic solvent, or the water and the organic solvent, and the lubricating component is characterized by comprising a base oil and a resin binder.
[0008] In the present invention, the resin binder preferably has a polar functional group. Further, in the present invention, the polar functional group preferably contains one or more selected from a urethane bond, a carbamoyl group, an amide group, an amine group, an ammonium group, a phosphoric acid group, or an organic acid group such as a carboxylate group, a nitro group, and a sulfonate group.
[0009] Further, in the present invention, the resin binder preferably contains one or more selected from an amide-based resin, an olefin-based resin, or a urethane-based resin. Furthermore, the present invention may further contain solid particles. [Effects of the Invention]
[0010] The lubricating composition of the present invention is excellent in lubricity and peel resistance. [Modes for Carrying Out the Invention]
[0011] Hereinafter, one embodiment of the present invention (hereinafter abbreviated as "embodiment") will be described in detail. The present invention is not limited to the following embodiments, and various modifications can be made within the scope of the gist thereof. In addition, the notation "~" includes both the lower limit value and the upper limit value as the range.
[0012] <Background Leading to the Present Embodiment> Conventionally, the properties required for diluted lubricating compositions applied to sliding parts such as automotive parts and precision equipment are to have excellent lubricity and to be resistant to film peeling under usage environments.
[0013] By the way, a fluorine solvent-diluted lubricating composition is known as an example of a diluted lubricating composition, but in a reciprocating sliding test performed using the fluorine solvent-diluted lubricating composition, it was confirmed that abnormal noise occurred before the number of sliding cycles reached 10,000. As described above, the lubricity deteriorated.
[0014] In addition, the coating film formed of the diluted lubricating composition is exposed to usage environments such as high temperature and high humidity, and the installation surface of the coating film is not limited to a flat surface, but may be various surfaces including an inclined surface, a vertical surface, and an uneven surface. Even under such a usage environment, it was required that the film be less likely to peel off. Accordingly, the present inventors have optimized the lubricating component to be diluted in a solvent, and have consequently developed a lubricating composition excellent in lubricity and peel resistance.
[0015] <Lubricating Composition in the Present Embodiment> The lubricating composition of the present embodiment includes a solvent, and a base oil and a resin binder as lubricating components.
[0016] (Solvent) The lubricating composition of the present embodiment contains water or an organic solvent as an essential component as a solvent. The content of the solvent is not limited, and the amount is not particularly restricted as long as the lubricating component can be diluted. For example, when only water is used as the solvent, the content is 60 mass% or more and 95 mass% or more, and preferably 70 mass% or more and 90 mass% or less, when the total amount of the lubricating composition is taken as 100 mass%.
[0017] In the present embodiment, the solvent may contain only water, or may contain only an organic solvent. Alternatively, a mixture of water and an organic solvent may be used. The organic solvent is not particularly limited as long as it is soluble or dispersible in water, but as an example of the index thereof, the solubility parameter (hereinafter, referred to as SP value) is 9 (J / cm 3 ) 1 / 2 It is preferable to use the above organic solvent. Here, the term "dispersed" means that the state of dispersion is maintained for 5 minutes or more by manual shaking.
[0018] The SP value is 9 (J / cm 3 )1 / 2 The type of the above organic solvent is not particularly limited, and for example, alcohol-based or glycol-based solvents can be preferably used. An SP value of 9 (J / cm 3 ) 1 / 2 Examples of the above organic solvent include ethyl acetate (SP value of approximately 9 (J / cm 3 ) 1 / 2 )), acetone (SP value of approximately 10 (J / cm 3 ) 1 / 2 )), methyl cellosolve (SP value of approximately 10 (J / cm 3 ) 1 / 2 )), and ethanol (SP value of approximately 13 (J / cm 3 ) 1 / 2 )), 1-butanol (SP value of approximately 11.4 (J / cm 3 ) 1 / 2 )), etc., which can be used by mixing with water. Incidentally, the SP value of water is approximately 23 (J / cm 3 ) 1 / 2 ). When alcohol is used as the organic solvent, it is preferably a lower alcohol, and suitably has 4 or less carbon atoms.
[0019] When only an organic solvent is used as the solvent, the content is 80 mass% or more and 99 mass% or less, preferably 90 mass% or more and 98 mass% or less, based on 100 mass% of the entire lubricating composition. Even when an organic solvent is used as the solvent, the environmental impact can be reduced by using bioalcohol produced from a biomass-derived raw material.
[0020] In addition, the total amount of the organic solvent and water as the solvent is not limited, and the amount is not restricted as long as the lubricating component can be diluted. Based on 100 mass% of the entire lubricating composition, the total content is 70 mass% or more and 99 mass% or less, preferably 80 mass% or more and 98 mass% or less. At this time, the content of the organic solvent alone is about 20 mass% to 60 mass%, or about 30 mass% or more and 55 mass% or less. From the viewpoint of safety, when alcohol is used as the organic solvent, the content is preferably less than 60 mass%, more preferably 55 mass% or less, and even more preferably 50 mass% or less.
[0021] (Base oil) The base oil is an essential component as a lubricant. It may also be a surfactant that can be dissolved, dispersed, or temporarily dispersed by stirring in water or an organic solvent. In this embodiment, it is preferable that the base oil does not contain fluorine oil, which is not easily decomposed in the environment.
[0022] While not limiting the kinematic viscosity of the base oil, within a temperature range of 20°C to 60°C, 20 mm 2 / s~1500mm 2 / s, 20mm 2 / s~1000mm 2 Approximately / s, or 20mm 2 / s~700mm 2 Approximately / s, or 20mm 2 / s~500mm 2 Approximately / s, or 20mm 2 / s~300mm 2 Approximately / s, or 20mm 2 / s~200mm 2 A viscosity of approximately / s is preferable. When mixing multiple base oils, the kinematic viscosity of the mixed oil should be adjusted within the above range.
[0023] The base oil preferably contains one or more of the following: glycol oil, glycol derivatives, ester oil, polyether-modified silicone oil, and hydrocarbon oil.
[0024] While not limited to these, the glycol oil can be polyoxyalkylene monobutyl ether, polyoxyethylene alkyl ether, or polyoxyethylene polyoxypropylene glycol. The glycol derivative can be polyalkylene glycol derivative or acetylene glycol derivative. For the ester oil, for example, sorbitan ester can be selected, and as such, sorbitan monocaprylate, sorbitan monolaurate, or sorbitan monooleate can be used. Furthermore, the hydrocarbon oil can be polyalphaolefin, ethylene propylene block copolymer, mineral oil, or animal / vegetable oil.
[0025] While there is no limit to the base oil content, it is preferable that the base oil content be between 1% and 25% by mass, or between 1% and 18% by mass, or between 1% and 15% by mass, when the entire lubricating composition is considered as 100% by mass. Furthermore, when mixing multiple types of base oil, the total value should be adjusted to fall within the above content range.
[0026] (Resin binder) In this embodiment, a resin binder is included as an essential component. By mixing in the resin binder, lubricity and peel resistance can be improved.
[0027] By adding a resin binder, improved adsorption can be expected, contributing to improved peel resistance. In particular, in lubricating compositions mixed with solid particles, as described later, the adhesion of the solid particles can be increased, resulting in improved peel resistance. Furthermore, the resin binder exhibits excellent dispersibility in solvents, allowing the lubricating components to be formed as a thin film on the material, thus enabling the creation of a coating film with superior lubricity.
[0028] The resin binder preferably has polar functional groups. This allows for better adsorption and improved dispersibility in the solvent, enabling the formation of a thin coating film with excellent peel resistance and lubricity.
[0029] While not limited to these, the polar functional group preferably includes one or more of the following: urethane bonds, carbamoyl groups, amide groups, amine groups, ammonium groups, phosphate groups, or organic acid groups such as carboxylate groups, nitro groups, and sulfonate groups. Including one or more of these polar functional groups can more effectively improve lubricity and peel resistance.
[0030] The resin binder preferably contains one or more of the following: amide resins, olefin resins, or urethane resins. The amide and urethane groups contained in the amide and urethane resins are polar functional groups. The olefin resin has a chemical structure to which polar functional groups are added. The olefin resin is an acid-modified olefin resin, for example, an acid-modified olefin amine salt, an acid-modified olefin ammonium salt, or an acid-modified olefin sodium salt. The resin binder can be selected from one or more of the amide resins, olefin resins, or urethane resins, or it is possible to mix one or more of the amide resins, olefin resins, or urethane resins with another resin binder. Of the polar functional groups mentioned above, the carboxylate group corresponds to the acid portion of the acid-modified olefin. For example, sodium carboxylate is ionized in water, and it is expected that the carboxylate group will be adsorbed when the water dries after application. Since sodium is thought to recombine when the water dries, it can also be interpreted as sodium carboxylate being attached. Furthermore, the acid portion could be phosphoric acid, boric acid, sulfuric acid, nitric acid, or an organic acid.
[0031] While there is no limit to the resin binder content, it is preferable that the resin binder content is 0.001% to 20% by mass, or 0.01% to 15% by mass, or 0.02% to 10% by mass, when the entire lubricating composition is considered to be 100% by mass. Furthermore, when the lubricating components (including base oil and resin binder) excluding the solvent are considered to be 100% by mass, it is preferable that the resin binder content is 0.1% to 90% by mass, or 0.5% to 85% by mass, or 1% to 80% by mass.
[0032] Although resin binders may take the form of solid particles, they are distinguished from the solid particles described below. For example, the diameter of a resin binder is significantly smaller than the diameter of the solid particles described below. That is, they can be distinguished by a difference in diameter of one or two orders of magnitude. Furthermore, as mentioned above, resin binders are preferably amide resins, olefin resins, or urethane resins, and materials made from these materials can be recognized as resin binders.
[0033] (solid particles) The lubricating composition of this embodiment can consist of a solvent and a base oil and resin binder as lubricating components, but may further contain solid particles.
[0034] Conventionally, the inclusion of solid particles resulted in significant noise generation even with a small number of sliding cycles. This is because sliding causes the solid particles to detach. In contrast, in this embodiment, the inclusion of a resin binder enhances the adsorption of the solid particles to the material. As a result, even with the inclusion of solid particles, detachment can be suppressed, and the generation of noise can be reduced.
[0035] The solid particles can be selected from, but are not limited to, resin particles. For example, at least one can be selected from polytetrafluoroethylene, polyethylene resin, or melamine cyanurate. The resin particles are preferably polytetrafluoroethylene or polyethylene resin.
[0036] Furthermore, the solid particles can be selected from wax particles, although this is not limited to them. For example, at least one can be selected from microcrystalline wax, FT synthetic wax, paraffin wax, montan wax, or plant-derived waxes such as carnauba wax or rice bran wax.
[0037] Furthermore, the solid particles may be inorganic particles having a cleavage structure. Examples of inorganic particles having a cleavage structure include, but are not limited to, molybdenum disulfide, carbon black, graphite, and boron nitride.
[0038] The solid particles may include two or more of the following: resin particles, wax particles, and inorganic particles having a cleavage structure. Mixing solid particles improves slipperiness and enhances lubricity. In particular, including resin particles and / or wax particles and / or inorganic particles having a cleavage structure can suppress stickiness after application and drying to parts, and reduce frictional force after drying. The solid particle content is approximately 0.001% to 10% by mass, or approximately 0.01% to 5% by mass, or 0.1% to 3% by mass or less, relative to the total lubrication composition.
[0039] Thus, even with the inclusion of solid particles, the resin binder can suppress peeling, and the inclusion of solid particles can promote a reduction in the coefficient of friction and extend the lifespan, resulting in a synergistic effect. Another effect of the resin binder is that it adsorbs to the solid particles, improving dispersibility in the solvent. The time it takes for components to separate over time differs significantly depending on whether or not the resin binder is added. In this way, it is expected that by adsorbing to the solid particles, the solid particles adhere to the material after coating and the solvent has dried, making them less prone to peeling.
[0040] The addition of solid particles may cause the coating film to exhibit color. On the other hand, if solid particles are not mixed, the coating film can be made transparent or nearly transparent. Therefore, the use of solid particles or not can be selected depending on the application of the lubricating composition of this embodiment. For example, in applications where the lubricating composition is applied to a location that is not visible from the outside and transparency is not required, adding solid particles to the lubricating composition to color the coating film makes it possible to identify the presence of the coating film and improves work efficiency. For example, in applications such as automotive parts, mixing solid particles to color the coating film makes it easier to confirm whether or not the coating has been applied even in hard-to-see locations, making it easier to prevent missed applications. Also, by looking at the color, it is possible to roughly estimate the amount of coating film, making it easier to ensure the desired lubrication performance.
[0041] (Preservative) The lubricating composition of this embodiment may include a solvent, a base oil and a resin binder as lubricating components, and a preservative. Alternatively, it may include a solvent, a base oil, a resin binder, solid particles, and a preservative.
[0042] While not limited to these, it is preferable to select thiazoline compounds or polyhydric alcohols as preservatives. Adding thiazoline compounds can improve both preservative effects and lubricity. In this specification, polyhydric alcohols refer to alcohols having two or more hydroxyl groups, and for example, sorbitan ester, which is described above as a base oil, falls into this category. Polyhydric alcohols are thought to act as oily agents and have the effect of reducing the coefficient of friction.
[0043] The reason why adding thiazoline compounds improves lubricity is, although this is purely speculation, likely because the formation of an adsorbent film reduces the coefficient of friction.
[0044] Experiments described later have shown that samples containing thiazoline compounds but without a resin binder exhibit reduced peel resistance. On the other hand, in this embodiment, which includes a resin binder, excellent peel resistance can be obtained even when a thiazoline compound is included.
[0045] While not limited to these, the thiazoline compound preferably contains one or more of the following: 1,2-benzothiazolin-3-one, 2-butyl-1,2-benzothiazolin-3-one, and 2-methyl-4-isothiazolin-3-one. Multiple different types of thiazoline compounds may be mixed. For example, 1,2-benzothiazolin-3-one and 2-methyl-4-isothiazolin-3-one can be mixed. This can define a synergistic effect of preservatives.
[0046] While there are no restrictions on the content of thiazoline compounds, it is preferable that the content is between 0.0001% by mass and 5% by mass, and between 0.001% by mass and 2% by mass, when the entire lubricating composition is considered as 100% by mass. It is preferable that the content of thiazoline compounds be less than the content of the base oil. The content of thiazoline compounds can be less than half the content of the base oil.
[0047] (Other additives) In this embodiment, colorants, antioxidants, rust inhibitors, oiliness agents, wear inhibitors, extreme pressure agents, etc., may be added to the lubricating composition of this embodiment as needed. The total content of these additives is kept within the range of approximately 0.001% to 10% by mass, or approximately 0.001% to 5% by mass, or approximately 0.001% to 3% by mass, relative to the total.
[0048] As mentioned above, the presence of solid particles can cause the coating film to become colored. However, if coloring is desired in a composition without solid particles, or if solid particles are included but a specific color is desired, a small amount of coloring agent can be added. Existing components can be used as coloring agents. Antioxidants can be selected from hindered phenol, triphenol, alkylated diphenylamine, ascorbic acid, phenyl-α-naphthylamine, etc. Rust inhibitors can be selected from sodium nitrite, sodium benzoate, carboxylic acids such as stearic acid, dicarboxylic acids, metal soaps, carboxylic acid amine salts, metal salts of heavy sulfonic acid, or carboxylic acid partial esters of polyhydric alcohols, benzotriazole, etc. Oiliness agents can be selected from amines such as laurylamine, higher alcohols such as myristyl alcohol, higher fatty acids such as palmitic acid, fatty acid esters such as methyl stearate, or amides such as oleylamide, etc. Anti-wear agents can be selected from zinc-based, sulfur-based, phosphorus-based, amine-based, or ester-based agents, etc. Extreme pressure additives can be selected from zinc dialkyldithiophosphate, molybdenum dialkyldithiophosphate, sulfurized olefins, sulfurized oils and fats, etc.
[0049] <Regarding the effects of using the lubricating composition in this embodiment> By using the lubricating composition of this embodiment on sliding parts, a thin film with excellent lubricity and peel resistance can be formed.
[0050] For example, the lubricating composition of this embodiment can be diluted with water, and unlike fluorine solvent-diluted lubricating compositions, components that are a concern for adverse environmental impacts are not released without decomposition, thus providing an environmentally friendly lubricating composition.
[0051] The lubricating composition in this embodiment can improve the lubrication between two components by being applied to sliding spaces such as resin-resin, resin-rubber, resin-metal, rubber-metal, metal-metal, rubber-rubber, rubber-leather, leather-leather, leather-resin, and leather-metal. Improved lubrication leads to better sliding and suppresses the generation of squeaking noises. Furthermore, it improves peel resistance, making film delamination less likely under various usage environments and extending the service life.
[0052] The surface on which the coating film is applied is not necessarily flat; it can be inclined or vertical, and it can also be a dynamic surface subject to vibration or rotation. Furthermore, the operating environment is not always constant and may change to high temperature and high humidity environments. Even under these operating conditions, this embodiment provides excellent peel resistance.
[0053] The lubricating composition of this embodiment, by including a resin binder, can enhance the adsorption force of solid particles to the material, even if it further contains solid particles, thereby eliminating problems such as the release of solid particles that cause squeaking noises and peeling of the coating film. As a result, the effects of reducing the coefficient of friction and extending the lifespan due to the inclusion of solid particles can be obtained synergistically.
[0054] Furthermore, the lubricating composition in this embodiment is also effective as an insertion aid for rubber components such as grommets, hoses, and sealants.
[0055] In other words, when passing cables or tubes through rubber, or when fitting rubber as a sealing material into a component, if nothing is applied, the frictional force is high and insertion becomes impossible. Generally, there is a demand for insertion aids, such as fluorine solvent-diluted lubricants, mineral oil, glycol oil, or organic solvents, to facilitate insertion. Fluorine solvent-based lubricants had problems such as requiring force to insert and being expensive.
[0056] Furthermore, while conventional oils and organic solvents can improve insertability, there are concerns that they may cause the rubber to swell and become more prone to coming loose, or that the durability of the rubber may deteriorate. Alternatively, oils may become sticky and transfer to other surfaces, potentially contaminating the area around the component.
[0057] In contrast, the embodiment in which water is the main component can suppress swelling and deterioration of rubber, and has excellent insertability. Furthermore, as the solvent dries after application, the amount of active ingredients decreases, which can suppress rubber slippage and also reduce stickiness.
[0058] Let's further consider the applications of rubber for lubrication. For example, there are applications where friction is reduced only immediately after application, such as when press-fitting hoses, while in other cases, such as with grommets, lubrication is required even after application and drying. To give one example, the timing of assembly to the vehicle body may involve applying lubricant to the parts, waiting a while, and then fitting the parts into place.
[0059] Traditionally, for example, oil was applied to parts to make them slide, but this often resulted in stickiness and oil dripping, raising concerns about contamination of surrounding components.
[0060] In particular, the inclusion of a resin binder or solid particles provides an effect of suppressing stickiness after application and drying. That is, stickiness can be suppressed and frictional force can be reduced after the lubricating composition dries. It is also effective as a rubber lubricant.
[0061] <Application> While not limiting its applications, the lubricating composition of this embodiment can be applied to automotive interior parts, precision instruments, ballpoint pens, and interior building materials for lubrication purposes, such as insertion aids, mold release agents, or rubber lubricants. In this embodiment, the lubricating composition can be applied both when at least some of the solvent remains after application to the parts, and when the lubricating composition has been applied to the parts and dried. Examples of automotive interior parts include seats, weatherstrips, grommets, etc. Examples of precision instruments include cameras, etc. Among these, it is particularly preferably applied to automotive interior parts. [Examples]
[0062] The present invention will be described in detail below with reference to examples implemented to clarify its effects. However, the present invention is not limited in any way by the following examples.
[0063] Comparative Examples 1-6 and Examples 1-30 were prepared. The raw materials used in each sample are shown in Tables 1, 2, 3, and 4. Comparative Example 7 is an experiment without coating.
[0064] Comparative Example 1 is a fluorine solvent-diluted lubricating composition. Comparative Examples 2 to 6 do not contain a resin binder. Examples 1 to 30 include at least a base oil and a resin binder as lubricating components.
[0065] The component content of each sample is shown in Tables 1 to 4, and the unit is mass percent.
[0066] In the experiment, each sample was prepared by mixing the components shown in Tables 1 to 4, and its peel resistance and lubricity were examined. In the experiments shown in Table 1, the following high-temperature and high-humidity tests and reciprocating sliding tests-1 were performed.
[0067] [High temperature and high humidity test and reciprocating sliding test - 1] Each sample's lubricating composition was applied once to the surface of a polyacetal (POM) plate using a brush and allowed to dry for 1 hour.
[0068] In the high-temperature and high-humidity test, the coated surface was left standing vertically for two days under conditions of 80°C and 95% Rh humidity. Then, it was checked whether or not peeling occurred in the coated film, and ○ was used to indicate no peeling, and × to indicate peeling.
[0069] [Reciprocating sliding test - 1] A polyacetal pin with a diameter of 4 mm was butted against the coated surface of the sample under a load of 100 g. A reciprocating sliding test was performed with a sliding distance of 10 mm, a sliding speed of 20 mm / s, and 10,000 sliding cycles.
[0070] In the reciprocating sliding test, we observed whether or not abnormal noise occurred during 10,000 sliding cycles, and determined the number of sliding cycles at which the abnormal noise first occurred. A "○" was used if no abnormal noise occurred up to 10,000 sliding cycles, and a "×" was used if abnormal noise occurred before reaching 10,000 sliding cycles. The number to the right of the "×" indicates the number of sliding cycles at which the abnormal noise occurred. The average coefficient of friction over 10,000 sliding cycles was also calculated.
[0071] [Table 1]
[0072] In the experiments shown in Table 2, the following high-temperature and high-humidity tests and reciprocating sliding tests-2 were performed.
[0073] [High temperature and high humidity test and reciprocating sliding test - 2] Each sample's lubricating composition was applied once to the surface of a polyacetal (POM) plate using a brush and allowed to dry for 1 hour.
[0074] In the high-temperature and high-humidity test, the coated surface was left standing vertically for two days under conditions of 80°C and 95% Rh humidity. Then, it was checked whether or not peeling occurred in the coated film, and ○ was used to indicate no peeling, and × to indicate peeling.
[0075] [Reciprocating sliding test - 2] A polyacetal sphere with a diameter of 10 mm was butted against the coated surface of the sample under a load of 200 g. A reciprocating sliding test was performed with a sliding distance of 40 mm, a sliding speed of 20 mm / s, and 10,000 sliding cycles.
[0076] In the reciprocating sliding test, we observed whether or not abnormal noise occurred during 10,000 sliding cycles, and determined the number of sliding cycles at which the abnormal noise first occurred. A "○" was used if no abnormal noise occurred up to 10,000 sliding cycles, and a "×" was used if abnormal noise occurred before reaching 10,000 sliding cycles. The number to the right of the "×" indicates the number of sliding cycles at which the abnormal noise occurred. The average coefficient of friction over 10,000 sliding cycles was also calculated.
[0077] Reciprocating sliding test-2 uses a polyacetal ball and differs from reciprocating sliding test-1. In addition, because a ball is used in reciprocating sliding test-2, the contact area is small and the load is large at 200g, resulting in high surface pressure and making the conditions stricter than in reciprocating sliding test-1.
[0078] [Table 2]
[0079] In the experiments shown in Table 3, the high-temperature and high-humidity test described above and the reciprocating sliding test-3 described below were performed. The experimental conditions for the high-temperature and high-humidity test were the same as those shown in Table 1.
[0080] [Reciprocating sliding test - 3] Each sample's lubricating composition was applied once to the surface of a polyacetal (POM) plate using a brush and allowed to dry for 1 hour. A polyacetal sphere with a diameter of 10 mm was butted against the coated surface of the sample under a load of 2000 g. A reciprocating sliding test was performed with a sliding distance of 40 mm, a sliding speed of 20 mm / s, and 10,000 sliding cycles.
[0081] In the reciprocating sliding test, we observed whether or not abnormal noise occurred during 10,000 sliding cycles, and determined the number of sliding cycles at which the abnormal noise first occurred. A "○" was used if no abnormal noise occurred up to 10,000 sliding cycles, and a "×" was used if abnormal noise occurred before reaching 10,000 sliding cycles. The number to the right of the "×" indicates the number of sliding cycles at which the abnormal noise occurred. The average coefficient of friction over 10,000 sliding cycles was also calculated. In reciprocating sliding test-3, the load was set to 2000g, making the conditions more stringent than in reciprocating sliding test-2.
[0082] [Table 3]
[0083] In the experiment shown in Table 4, the following reciprocating sliding test-4 was performed.
[0084] [Reciprocating sliding test - 4] Each lubricating composition shown in Table 4 was applied once to the surface of an EPDM rubber sheet using a brush. A 4mm diameter stainless steel pin was then butted against the sample surface with a load of 500g, and the sliding distance was set to 10mm and the sliding speed to 20mm / s. The average coefficient of friction over 10 trials was measured immediately after application (before the solvent dried) and the following day (after the solvent dried).
[0085] [Table 4]
[0086] [Regarding the comparative example] As shown in Tables 1 to 3, in Comparative Examples 1 to 6, at least one of the high-temperature and high-humidity tests or the reciprocating sliding test was evaluated as "fail".
[0087] Comparative Example 1 was a fluorine solvent-diluted lubricating composition. While it exhibited good peel resistance, it had poor lubrication and produced abnormal noise.
[0088] Comparative Examples 2 and 3 were lubricating compositions using water as the solvent. While they exhibited good lubricity, their peel resistance deteriorated. Comparative Examples 2 and 3 contained thickeners and preservatives (thiazoline compounds), and it is believed that the reduced adhesion to the material at high temperature and high humidity led to the decreased peel resistance.
[0089] Comparative Example 4 is a sample in which the water content was reduced from Comparative Example 2, and instead solid particles were included, but both the peel resistance and lubricity deteriorated.
[0090] Comparative Example 7, shown in Table 4, is a reference case in which the sample is not applied to the surface of the plate.
[0091] [Examples] In contrast, Examples 1 to 26, shown in Tables 1 to 3, received a "○" rating in both the high-temperature and high-humidity test and the reciprocating sliding test.
[0092] Examples 1 to 26 include a resin binder. It was found that this improves both peel resistance and lubricity.
[0093] For example, Comparative Example 5 and Example 4 in Table 2 have the same components except for the presence or absence of a resin binder. Example 4 is a sample in which the water content of Comparative Example 5 is reduced and that amount is replaced by the resin binder content.
[0094] Significant differences in peel resistance and lubricity were observed between Example 4 and Comparative Example 5. In Comparative Example 5, peeling was observed in the high humidity and high temperature test, and abnormal noise occurred after several dozen sliding cycles in the sliding test, whereas in Example 4, no peeling was observed, and no abnormal noise occurred even after more than 10,000 sliding cycles.
[0095] Furthermore, Comparative Example 6 and Example 23 in Table 3 have the same components except for the presence or absence of a resin binder. Example 23 is a sample in which the water content of Comparative Example 6 was reduced and that amount was replaced with the resin binder content.
[0096] Significant differences were observed in peel resistance and lubricity between Example 23 and Comparative Example 6. In Comparative Example 6, peeling was confirmed in the high humidity and high temperature test, and abnormal noise occurred after several dozen sliding cycles in the sliding test, whereas in Example 23, no abnormal noise occurred even after more than 10,000 sliding cycles.
[0097] The only difference between Example 4 and Comparative Example 5, and between Example 23 and Comparative Example 6, is the presence or absence of a resin binder. This indicates that the inclusion of a resin binder improved peel resistance and lubricity. In particular, the experiments in Table 2 and Table 3 had more stringent reciprocating sliding test conditions compared to the experiments in Table 1, but even under these stringent reciprocating sliding conditions, the inclusion of a resin binder effectively improved lubricity.
[0098] Examples 21 and 22, shown in Table 2, were identical except for the type of thickener used in the mixture, but no significant difference was observed in their peel resistance and lubricity.
[0099] Examples 4, 16, and 27-30, shown in Table 4, were able to reduce the coefficient of friction both immediately after application and the day after application, compared with Comparative Example 7, which served as a reference. Furthermore, when comparing Examples 4, 16, and 27-30 with Comparative Example 2, there was not much difference in the coefficient of friction immediately after application, but a significant difference was observed in the coefficient of friction the day after application, with Examples 4, 16, and 27-30 all being significantly lower than Comparative Example 2. It was found that the inclusion of a resin binder or solid particles could suppress stickiness and reduce frictional force.
[0100] [About the solvent] Example 1 contains only an organic solvent as the solvent, for example Example 4 contains only water as the solvent, for example Example 2 contains water and an organic solvent as the solvent. Therefore, it was found that any form in which the solvent is water, or an organic solvent, or a mixture of water and an organic solvent, is considered an example.
[0101] [About base oil] Base oil is an essential component as a lubricant. A single type of base oil may be used, or a mixture of multiple types may be used. As shown in the examples, the base oil does not contain fluorine oil. The kinematic viscosity of the base oil is 20 mm² at temperatures between 20°C and 60°C. 2 / s~1000mm 2 It was around / s.
[0102] Furthermore, it was found that the base oil preferably contains one or more of the following: glycol oil, glycol derivatives, polyether-modified silicone oil, hydrocarbon oil, and ester oil.
[0103] Tables 1 to 3 show that many samples contain more base oil than resin binder, but in Example 6, the resin binder is present in a larger quantity than the base oil.
[0104] The base oil content is approximately 1 to 15% by mass. Since the base oil, as an oil component, is the main component in the coating film, it can be included in a large amount. By mixing it with a resin binder, a strong coating can be formed.
[0105] [About resin binders] The experimental results shown in Tables 1 to 3 demonstrate that the addition of a resin binder effectively improves peel resistance and lubricity. Furthermore, the experimental results shown in Table 4 show that frictional force can be reduced.
[0106] All resin binders used in the experiment were resin binders containing polar functional groups. The experiments used binder resins with chemical structures containing urethane bonds, carbamoyl groups, amide groups, amine groups, ammonium groups, phosphate groups, or organic acids such as carboxylate groups, nitro groups, and sulfonate groups as polar functional groups. The specific names of the resins are shown in the respective tables.
[0107] The resin binder content was set to 20% by mass or less, or 15% by mass or less, or 10% by mass or less. This makes it possible to obtain the desired lubricity and peel resistance effects.
[0108] The amide resins shown in Table 1 are soluble in alcohol, and in Examples 1 to 3, ethanol was used as the organic solvent. The resin binders used in the experiments, with the exception of the amide resins, were in the form of solid particles with diameters of approximately 0.1 μm or 1.0 μm. However, the diameters of the other resin binders, excluding copolymerized nylon, were approximately 0.1 μm. This diameter is very small, and it was found that the solid particles in the "Classification" column of Tables 1 to 4 have a diameter significantly larger than that of the resin binders. The diameters of the solid particles in the "Classification" column of Tables 1 to 4 ranged from approximately 0.3 μm to 10 μm. The diameter of the solid particles constituting the resin binders is approximately 0.01 μm to 1 μm, preferably 0.03 μm to 0.5 μm, more preferably 0.05 μm to 0.3 μm, and even more preferably 0.07 μm to 0.2 μm.
[0109] [About solid particles] In some embodiments, solid particles were added. The solid particles used in the experiments were resin particles and wax particles. In this embodiment, the inclusion of a resin binder suppressed the generation of abnormal noise even when additional solid particles were added.
[0110] Furthermore, for example, Example 5 shown in Table 1 is a sample in which the base oil content of Example 4 was reduced and solid particles were added accordingly. Comparing Example 4 and Example 5, both lubricity and delamination properties were good, but the coefficient of friction was lower in Example 5 than in Example 4. Thus, it was found that the coefficient of friction can be reduced by including solid particles. The content of solid particles was approximately 0.1% to 3% by mass relative to the total lubricating composition.
[0111] [About preservatives] In Examples 1-19 and 23-30, thiazoline compounds were mixed in as preservatives. Thiazoline compounds have both preservative and lubricity-improving effects. On the other hand, in Comparative Examples 2-6, which did not contain a resin binder, peel resistance deteriorated. Therefore, as in this embodiment, by including a resin binder and a thiazoline compound, it was possible to obtain lubricating, peel-resistant, and preservative effects.
[0112] The content of the thiazoline compound was 5% by mass or less, preferably 2% by mass or less, and more preferably 1% by mass or less. [Industrial applicability]
[0113] The lubricating composition of the present invention is preferable to fluorine solvent-diluted lubricating compositions for use in automotive parts and sliding parts of precision equipment. By using the lubricating composition of the present invention, both lubricity and peel resistance can be improved. Therefore, it is possible to obtain high-quality lubrication performance with consideration for safety for the above-mentioned automotive parts and precision equipment.
Claims
1. It comprises at least a solvent and a lubricating component, The solvent comprises water, an organic solvent, or the water and the organic solvent. The aforementioned lubricating component comprises a base oil, a resin binder, A lubricating composition characterized by containing the following:
2. The lubricating composition according to claim 1, characterized in that the resin binder has polar functional groups.
3. The lubricating composition according to claim 2, characterized in that the polar functional group includes one or more of the following: a urethane bond, a carbamoyl group, an amide group, an amine group, an ammonium group, a phosphoric acid group, or an organic acid such as a carboxylate group, a nitro group, or a sulfonate group.
4. The lubricating composition according to claim 2 or 3, characterized in that the resin binder contains one or more of amide resins, olefin resins, or urethane resins.
5. Furthermore, the lubricating composition according to claim 1, characterized in that it further contains solid particles.
Citation Information
Patent Citations
Lubricant composition
JP2010184995A
Solvent-diluted fluorine-based lubricant composition
JP2020105329A